2009
DOI: 10.1111/j.1464-5491.2008.02638.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating CD34+ cells are associated with progression of diabetic nephropathy

Abstract: These results suggest that a decreased number of circulating CD34+ cells is involved in the progression of diabetic nephropathy and may be a predictor of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 10 publications
1
23
0
8
Order By: Relevance
“…22 Moreover, decreased secretion of NO and vascular endothelial growth factor (VEGF), reduced activity of superoxide dismutase, and impaired function, such as migration and tube formation, are observed in activated late EPCs after exposure to a hyperglycemic condition 23 or advanced glycation end products. 24 Reduced number and function of EPCs are also more prevalent in patients with type 1 and type 2 DM with diabetic nephropathy [25][26][27][28] and macrovascular 26,[29][30][31][32][33] complications and correlate with the degree of atherosclerosis. 34 These observations suggest that the burden of DM-related cardiovascular complications correlates with the number and function of EPCs: alterations in EPCs may contribute to the development and progression of atherosclerosis in patients with DM.…”
Section: Yiu and Tse Diabetes Mellitus And Endothelial Progenitor Celmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Moreover, decreased secretion of NO and vascular endothelial growth factor (VEGF), reduced activity of superoxide dismutase, and impaired function, such as migration and tube formation, are observed in activated late EPCs after exposure to a hyperglycemic condition 23 or advanced glycation end products. 24 Reduced number and function of EPCs are also more prevalent in patients with type 1 and type 2 DM with diabetic nephropathy [25][26][27][28] and macrovascular 26,[29][30][31][32][33] complications and correlate with the degree of atherosclerosis. 34 These observations suggest that the burden of DM-related cardiovascular complications correlates with the number and function of EPCs: alterations in EPCs may contribute to the development and progression of atherosclerosis in patients with DM.…”
Section: Yiu and Tse Diabetes Mellitus And Endothelial Progenitor Celmentioning
confidence: 99%
“…28,35,59,72 Glucagon-like peptide-1 agonist and DPP-4 inhibitors are a newer class of antidiabetic agents that act by increasing the Figure 2. Potential therapeutic avenues to restore endothelial progenitor cell (EPC) number and functions for the prevention of macrovascular and microvascular complications in diabetes mellitus (DM).…”
Section: Antidiabetic Agentsmentioning
confidence: 99%
“…У пациентов с большим количеством CD34+ клеток экскреция альбумина не изме-нилась в течение 12 мес. Исследователи пришли к выводу, что циркулирующие CD34+ клетки участвуют в прогрес-сировании ДН, и данный показатель можно использовать в качестве прогностического маркера ДН [35]. В другом исследовании также показано, что количество циркулиру-ющих CD34+ и CD34+CD133+ клеток ниже у пациентов с МАУ по сравнению с пациентами без МАУ.…”
Section: эпк и осложнения сдunclassified
“…Снижение количества клеток коррелирует с наличием МАУ [28] и прогнозирует прогрессирование МАУ [35]. Снижение количества клеток и нарушение их функции коррелируют с наличием МАУ [28].…”
Section: Cd34+cd133+unclassified
“…Interestingly, at the early stage of metabolically inactive obesity ("not fully" metabolic syndrome) BM-EPCs number may increase and an ability of primitive cells to mobbing, differentiation and colony forming might be not distinguished healthy individuals [66]. In contrast, development of insulin resistance, metabolic syndrome and type 2 DM has closely associated with weak ability of EPCs to mobbing, and the lowered level of circulating EPCs was determined [67]. In contrast, Asnaghi V et al (2006) [68] have reported that clonogenic potential of circulating EPCs in patients with type 1 DM may increase.…”
Section: Endothelial Progenitor Cells and CV Riskmentioning
confidence: 99%